Degradation of Sol-Gel Acrylic Coatings Based on Si and Zr Investigated Using Electrochemical Impedance, Infrared and X-Ray Photoelectron Spectroscopies - Rodič, Peter; Zanna, Sandrine; Milošev, Ingrid; Marcus, Philippe (Frontiers in Materials, 2021)
This study aimed to synthesise and characterise two types of sol-gel acrylic coatings: one based on Si and the other based on Si and Zr. These coatings, which served as barrier for corrosion protection of aluminium, were synthesised by sol-gel methodology using silicon precursors tetraethyl orthosilicate and organically modified silicon precursor 3-methacryloxypropyltrimethoxysilane, without and with the addition of zirconium(IV) n-propoxide chelated with methacrylic acid. The synthesis process was followed using real-time Fourier transform infrared spectroscopy, which confirmed the condensation reactions of Si–O–Si and Si–O–Zr networks, depending on the sol type. This was reflected in the composition of the coating as well, as shown by X-ray photoelectron spectroscopy. The coating topography, thickness and morphology were analysed using focused ion beam scanning electron microscopy. X-ray photoelectron spectroscopy was employed to follow the degradation of acrylic coatings upon immersion in sodium chloride solution. Corrosion properties, evaluated using electrochemical impedance spectroscopy in 0.1 M NaCl, confirmed high barrier protection of coated aluminium with acrylic coatings based on Si and even better for coating based on Si with Zr. The more durable corrosion resistance of the latter was also confirmed by salt spray testing.